Analisa Kesalahan dalam Berbicara dan Berbahasa pada Diskusi Anak Sekolah Dasar Kelas III dengan Konsep Morfologis di Madrasah Ibtidaiyah Ali Imran Medan - Audina, Fitra; Khairunnisa, Siti; Syajida, Syajida; Atika, Rindi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to share an understanding of the use of proper language by third-grade students at Madrasah Ibtidaiyah Ali Imran Medan Elementary School. Many students have pronunciation errors that need to be studied in terms of the dictionary and morphology. The research method used is a descriptive qualitative research method with direct observation and observation of students at school. The results show that many third-grade students use standard language mixed with everyday language, so their pronunciation is not pleasant when applied, and they are used to using regional accents so that when pronunciation using Indonesian feels foreign. The purpose of this research is to help students speak in accordance with good and proper rules.